Ecotourism in Ghoda Ghodi Wetland Sukhad, Kailali, Nepal - Khadka, Dipak; Chaudhary, Ankita; Karki, Rubina; Sharma, Bishal; Bhatta, Sijar (Journal of Tourism and Hospitality Education, 2021)
Tourism is the act of spending time away from home. Nepal has remained an exotic tourist location for several decades, and wetlands are among the major areas of tourism in Nepal. Located in the far-western Tarai of Nepal, Ghoda Ghodi Lake is among the major wetlands in terms of both biodiversity and tourism. This study has assessed the ecotourism status in Ghoda Ghodi Lake of Nepal and to understand the current condition and possible inferences. A total of 40 households were surveyed, and 80 visitors were interviewed for collecting primary data. Most of the respondent visitors have visited wetlands more than five times. It is important to point out that fifty percent of the respondent visitors have visited the wetland for natural purposes indicating that the naturalness of the wetland has more capacity to attract tourists. Visitors perceived to enhance economic activities and increase employment opportunities to attract locals to promote ecotourism. The local people were engaged in homestay earning around NRs 2 to 4 lakh per year as well most of the local respondents (50%) were participating in tourism promotion activities.